Maternal and fetal angiotensinogen gene allele sharing in pre‐eclampsia - Morgan, L.; Crawshaw, S.; Baker, P. N.; Pipkin, F. Broughton; Kalsheker, N. (BJOG : an international journal of obstetrics and gynaecology, 1999)
Objective To compare the angiotensinogen genotypes in normotensive and pre‐eclamptic pregnancies in maternal and fetal samples. Design Prospective observational study. Setting University Hospital, Queen's Medical Centre, Nottingham. Population Forty‐three women with pre‐eclampsia and 84 normotensive pregnant women. Fetal samples were available for genotyping from 96% of the pregnancies. Methods Maternal and fetal DNA was genotyped at angiotensinogen codon 235 and at a dinucleotide repeat polymorphism in the 3′ flanking region of the gene. Angiotensinogen and renin concentrations were measured in maternal plasma by radioimmunoassay. Results In contrast to earlier studies, no association was demonstrated between the angiotensinogen 235 Thr variant and pre‐eclampsia. Normotensive pregnant women homozygous for this variant had significantly lower plasma angiotensinogen concentrations (median 2.2 ng AI/mL; IQR 1.8–3.0) than women homozygous for the 235 Met allele (3.6 ng AI/mL; IQR 2.5–4.1; P= 0.04). In pre‐eclamptic pregnancies, 79% (11/14) of mothers heterozygous for the dinucleotide repeat allele designated A9 transmitted this allele to the fetus, more frequently than would be expected by chance (P= 0.02). The A9 allele was associated with low plasma angiotensinogen concentrations (P= 0.001) and high renin concentrations (P= 0.02) in normotensive women. Conclusions There is no evidence that the angiotensinogen 235 Thr allele is associated with pre‐eclampsia in the Nottingham population. The angiotensinogen 235 Thr allele is associated with low plasma angiotensinogen concentrations in normotensive pregnant women, in contrast to the high levels associated with this variant in non‐pregnant women, suggesting that regulation of angiotensinogen expression in normal pregnancy may differ significantly from that in the non‐pregnant state. There is preliminary evidence that maternal‐fetal transmission of an angiotensinogen allele associated with low plasma angiotensinogen concentrations is associated with pre‐eclampsia. Impaired generation of angiotensin II at the maternal‐fetal interface may be a factor in the pathogenesis of pre‐eclampsia.